Peran Perbankan Syari’ah dalam Perkembangan Perekonomian di Indonesia - Habibi, Miftakhur Rokhman; Diah, Ruriana (Islamic Economic Law Programs, Faculty of Sharia and Law State Islamic University (UIN) of Sunan Ampel Surabaya., 2022)
The existence of institutions and all the rules in which there are matters of money in the running of finance in the country, have become the most important foundation and guidance in accelerating the speed of development of a country, especially in terms of the economy. Indonesia is a country with most people embracing Islam, certainly wants a mechanism as a financial regulator. while avoiding the interest system in banking. Islam embodies the basis of sharia trading. Islamic banks appear as an answer about the cons of usury and interest in banking. So, therefore, Indonesian Muslims who want their financial operations in banks to avoid usury, do not need to worry anymore with the existence of Islamic banks or Islamic banks. The banking sector is important as a link between capital and the real results that are in the hands of capital owners. The first use of banking in a large economy must be aimed at what ways that money can be used properly as a ranking of the economy. The existence of Islamic banks cannot be separated from the plummet of the economy which was initially seen and called the monetary crisis. Islamic Bank is a bank that in running its finances, leaving all the problems of usury. In this case, the interest that is considered as usury is a challenge in these times. Islamic finance exists, based on two reasons. Due to the prohibition of taking usury in it. And because of financial transactions that have it in it, is considered to have some shortcomings.